Online Learning Media on Science Learning during the COVID-19 Pandemic: A Literature Study in Indonesia - Widayanti, Widayanti (Online Learning In Educational Research (OLER), 2021)
This study aims to analyze online learning media used in science learning during the COVID-19 pandemic. This research uses a literature study method by conducting three stages of research, namely data collection, data analysis, and conclusions. This study analyzed 18 science journals in Indonesia. It is found that the science learning media used during the COVID-19 pandemic are e-modules, Google Classroom, smartphone sensors, and virtual laboratories through PhET and LiveWire. Each learning media application must be adjusted to the indicators and the level of education. The findings of this study can improve learning outcomes, learning motivation, critical thinking, problem-solving, concept mastery, and science process skills